Heidegger on Luther on Paul - Stanley, Timothy (Dialog, 2007)
When it comes to how Heidegger understands theology, Martin Luther was instrumental in his early formulations. Heidegger's interpretation of Luther leads him to descry theology as a discipline best left unfettered by metaphysics and this attitude is carried right through Heidegger's career. By explicating Luther's influence upon Heidegger's early Freiburg lectures from 1919-1923, we can raise important questions about the nuanced way Heidegger construes Luther's theology in the hopes of inspiring key insights for Luther's appropriation in current post-Heideggerian theology.